IMPLEMENTASI KEBIJAKAN BOP DITINJAU DARI TEORI EDWARD III UNTUK MENINGKATKAN EFEKTIVITAS PENGGUNAAN BOP DI SMK - Arianto Halawa, Atanasius; Sophia Tri Satyawati; Bambang Ismanto (P3M STKIP 'Aisyiyah Riau, 2023)
In this scientific writing, the researcher specifically examines the policy process ini education using Edward III theory to evaluate educational operational costs through communication and information obtained from the school principal as the person in charge and the treasurer as the manager of the BOP funds. The aim is to find out the concept of managing BOP funds through Edward III theoretical policy that BOP is assistance in the from of money provided by the government to support the implementation of a quality education process. The method used to obtain research result is through the use of descriptif qualitative research through interviews and observation. So the research result prove that policies in distributing BOP funds must include implementation planning management implementation and accountability evaluation.